Development of an expert system for the diagnosis of eye refractive disorders using a web-based certainty factor method case study: Optik Bringin Jogja - Julia Carenita Reri Ola; A. Sidiq Purnomo (Jurnal Mantik, 2026)
Refractive eye disorders—including myopia, hyperopia, astigmatism, and presbyopia—are a vision health problem whose prevalence continues to increase in Indonesia. However, public access to adequate examination facilities remains very limited. Frequent overlap in symptoms between one disorder and another complicates independent identification without expert assistance. This study aims to develop a web-based expert system that assists the public in conducting initial screening for refractive eye disorders using the Certainty Factor (CF) method, based on knowledge obtained through interviews with certified optical refractologists at Optik Bringin Jogja. The system was built using the PHP programming language with the Laravel framework and MySQL as the database management system, and can be accessed through a browser without additional installation. The CF method is applied to gradually calculate a diagnostic confidence value based on a combination of expert and user CF values for reported symptoms. Functional testing using the black-box method shows that all system features function as expected. Accuracy testing was conducted on 50 patient records from Optik Bringin Jogja, resulting in an accuracy rate of 92%, with 46 of 50 cases matching the system's diagnosis to the optical refractionist's diagnosis. The results of the study show that the Certainty Factor method is effective when applied to refractive disorders with overlapping symptoms, making it suitable as an initial screening tool before patients receive further treatment from experts.